Polyakov-quark-meson-diquark model for two-color QCD - Strodthoff, Nils; Smekal, Lorenz von (Physics letters, 2014)
We present an update on the phase diagram of two-color QCD from a chiral effective model approach based on a quark-meson-diquark model using the Functional Renormalization Group (FRG). We discuss the impact of perturbative UV contributions, the inclusion of gauge field dynamics via a phenomenological Polyakov loop potential, and the impact of matter backcoupling on the gauge sector. The corresponding phase diagram including these effects is found to be in qualitative agreement with recent lattice investigations.
Gesehen am 28.08.2020